Fucoxanthin protects retinal ganglion cells and regulates Parkin-mediated mitophagy in experimental glaucoma - Lifang Zhang; Dandan Wang; Qinkang Lu; Haixia Ma; Xinxin Hu; Juntao Zhang; Wei Lian (BMJ Open Ophthalmology)
Objective Glaucoma is a common neurodegenerative disease resulting in irreversible blindness. This study investigates whether fucoxanthin can safeguard retinal ganglion cells (RGCs) by modulating Parkin-mediated mitophagy in experimental glaucoma.Methods An experimental glaucomatous model was induced in Sprague-Dawley rats via translimbal laser photocoagulation. Intraocular pressure (IOP) was monitored using a Tonolab tonometer. RGC survival was evaluated through FluoroGold labelling. Retinal and optic nerve samples were analysed at 3 days and 2 weeks post-IOP elevation for mitochondrial morphology and gene/protein expression using immunohistochemistry and molecular assays.Results Results demonstrated that mitophagy was acutely overactivated in the short term and impaired over the long term in ocular hypertensive rats. Fucoxanthin intravitreal administration enhanced RGC survival and Bcl-2 expression while reducing Bax and glial fibrillar acidic protein levels. During acute IOP elevation, fucoxanthin curtailed Parkin expression and mitophagosome formation, mitigating excessive mitophagy. Under prolonged IOP elevation, it elevated mitophagy-related proteins and restored mitophagy function, contributing to damaged mitochondrial clearance.Conclusion Fucoxanthin exerts neuroprotective effects in experimental glaucoma by modulating Parkin-mediated mitophagy. This highlights the therapeutic potential of maintaining mitophagy homeostasis for glaucoma treatment.